2020
DOI: 10.30657/pea.2020.26.14
|View full text |Cite
|
Sign up to set email alerts
|

Non-uniform corrosion of steel rebar and its influence on reinforced concrete elements` reliability

Abstract: AbstractRemarkable place of reinforced concrete structures in construction field has been noted in wide number of recent researches. Subsequently, their degradation due to aggressive environment has become the topical problem nowadays. Therefore, the formulation of reliable technique for corroded element strength decrement is of great importance, and could be achieved only with the use of complex experimental and theoretical analysis. In this article an attempt is made to propo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
5

Relationship

5
5

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…In the works [ 16 , 17 ], the rate of rebar corrosion and the intensity (depth) of corrosion damages depending on width of opening of cracks were considered with the use of modern research methods.…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
“…In the works [ 16 , 17 ], the rate of rebar corrosion and the intensity (depth) of corrosion damages depending on width of opening of cracks were considered with the use of modern research methods.…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
“…The use of GGBFS and FA may also have an influence on the initial pH of the cementitious system and the protective passive layer, which is formed on the reinforcing steel bars due to the alkaline environment in concrete [ 35 ]. In the last few decades, corrosion of rebars in reinforced concrete structures is one of the main factors, which causes their extensive premature deterioration and has a serious effect on the serviceability and safety [ 36 , 37 ]. However, there have not been many publications in the literature related to the effect of the amount of SCMs on the corrosion susceptibility of reinforcing steel bars in concretes, in spite of the tendency of the significant reduction of clinker factor (CF) in cements to follow their contemporary tendencies.…”
Section: Introductionmentioning
confidence: 99%
“…However, the estimation of conditions which cause osmotic pressure in the cement stone and their possible role in corrosion destruction is realizable only on the basis of experiments for particular conditions. Studies of the role of magnesium compounds in the development of osmotic processes [ 19 ] have shown that concrete with increased density of cement mortar shows some signs of semi-permeability. When magnesium salts interact with calcium hydroxide, amorphous magnesium hydroxide is deposited in the pores of the concrete, which enhances the semi-permeability effect.…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%